Pengaruh Gaya Kepemimpinan Transformasional terhadap Kinerja Pegawai Kantor Desa Pematang Gajah, Kabupaten Muaro Jambi, dengan Etos Kerja sebagai Variabel Intervening - M. Bagus Subarkah; Rike Setiawati; Fitri Widiastuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This research was conducted with the aim of knowing and analyzing the influence of transformational leadership style on employee performance through work ethic as an intervening variable at the Pematang Gajah Village Office, Muaro Jambi Regency. The population in this study is all employees or village officials working at the Pematang Gajah Village Office, Muaro Jambi Regency, and a census technique was used for sampling with a total of 30 respondents. The method used in this study is the quantitative analysis method, with the data used in this study obtained through the questionnaire method. The data analysis tool in this study uses Structural Equation Modeling-Partial Least Square (SEM-PLS) in the SmartPLS 4.0 application. The results of this study indicate that transformational leadership style has a positive and significant effect on employee performance, and transformational leadership style has a positive and significant effect on work ethic. Work ethic has an influential and significant effect on employee performance. Transformational leadership style has a positive and significant effect on employee performance through work ethic as an intervening variable in Pematang Gajah Village, Muaro Jambi Regency.